Theoretical Principles of Developing for Effectiveness of Social Tourism Services - D. Norkulova (International Journal of Advanced Science and Technology, 2020)
This article indicates that one of the social effects of social tourism services is the social capital and its specific aspects, and the mechanism of distribution of social impacts is analyzed and a system of indicators that reflects the effectiveness of the development of social tourism services is proposed.